Beyond the genetic code in leaf senescence. (15th December 2017) - Yolcu, Seher; Li, Xiaojie; Li, Shengben; Kim, Yun Ju
Abstract : Leaf senescence, which is both endogenously programmed and stress-induced, is regulated by genetic factors in concert with multiple layers of epigenetic mechanisms and small RNA activity. Abstract: Leaf senescence is not only genetically programmed but also induced by exogenous stress to ensure completion of the plant life cycle, successful reproduction and environmental adaptability. Genetic reprogramming is a major aspect of leaf senescence, and the senescence signaling that follows is controlled by a complex regulatory network. Recent studies suggest that the activity of transcription factors together with epigenetic mechanisms ensures the robustness of this network, with the latter including chromatin remodeling, DNA modification, and RNA-mediated control of transcription factors and other senescence-associated genes. In this review, we provide an overview of the relevant epigenetic mechanisms and summarize recent findings of epigenetic regulators of plant leaf senescence involved in DNA methylation and histone modification along with the functions of small RNAs in this process.